Liikkuvat tekstit, liikkuvat naiset: Suomen, Venäjän ja Neuvostoliiton kirjallisella kentällä - Parente-Čapková, Viola; Rosenholm, Arja; Launis, Kati (Suomalaisen Kirjallisuuden Seura, 2026)
Texts on the Move – Women on the Move in the Literary Field of Finland, Russia, and the Soviet Union This volume examines the literary relations between Finland and Russia, focusing on the reception of women writers. Spanning two centuries, it takes us from the 1840s to today’s literary bloggers and digital media. “Reception” is understood broadly to include translations, press reviews, intertextual exchanges, and the physical presence of books in library collections. At the center of the book are the many women – past and present – who have transmitted ideas and ideologies: authors, translators, journalists, and scholars. The book is the outcome of long-term collaboration among seasoned researchers. It shows that women have always been vital literary intermediaries in both Russia and Finland. The volume brings to light numerous women writers and cultural actors who have long languished in the shadow of Russia’s male classics, thus opening up a new perspective on the history of literary reception. It not only enriches but also corrects the existing literary and cultural history between Finland, Russia, and the Soviet Union by generating new knowledge about the roles women have played. Methodologically, the contributors combine deep literary-historical expertise with the innovative use of digital corpora. The findings of the research project that this book introduces are gathered in an open-access database, which will serve future generations of historians and literary scholars. Written in the midst of crisis – while Russia continues its invasion in Ukraine – this book is all the more timely, as it is crucial to understand how culture, literature, and language are involved in creating geopolitical relations. Studying women writers’ oeuvres and reception, as well as their cultural and political activism, casts a new light on the conflicting images of Russia that Finnish readers have interpreted across different eras, often behind various masks and veils.